The Gut-Kidney-Heart Axis in Uremia: A Systematic Review of the Association Between Gut Dysbiosis and Cardiovascular Complications in End-Stage Renal Disease - Anggreini Oktavia Trisno; Chelsia Ernes (International Medical Journal Corp. Ltd, 2025)
Background: Patients with End-Stage Renal Disease (ESRD) experience an exceptionally high burden of cardiovascular morbidity and mortality that is not fully explained by traditional risk factors. The gut-kidney-heart axis has emerged as a critical pathophysiological paradigm, implicating gut dysbiosis and the resultant accumulation of gut-derived uremic toxins as key non-traditional risk factors for cardiovascular disease (CVD) in this population. Methods: A systematic literature search was conducted in PubMed, Google Scholar, Semantic Scholar, Springer, Wiley Online Library to identify observational studies investigating the association between markers of gut dysbiosis (microbial composition, diversity, and gut-derived metabolites including indoxyl sulfate, p-cresyl sulfate, trimethylamine N-oxide, indole-3-acetic acid [IAA], and phenylacetylglutamine [PAGln]) and cardiovascular complications in adult patients with ESRD. Study selection followed PRISMA guidelines. Data on study design, population characteristics, dysbiosis markers, and cardiovascular outcomes were extracted. The methodological quality of included studies was assessed using the Newcastle-Ottawa Scale. Results: Seventeen primary observational studies, comprising over 4,100 patients, were included. The evidence consistently demonstrated significant associations between gut dysbiosis and adverse cardiovascular outcomes. Lower gut microbial diversity was a strong predictor of all-cause and cardiovascular mortality. Elevated serum levels of IS, PCS, TMAO, IAA, and PAGln were independently associated with increased risks of all-cause mortality, cardiovascular mortality, major adverse cardiovascular events (MACE), heart failure, arterial stiffness, and vascular calcification. Furthermore, circulating endotoxin, a marker of intestinal barrier dysfunction, was linked to systemic inflammation, atherosclerosis, and myocardial injury. Discussion: The synthesized evidence supports a mechanistic cascade wherein the uremic milieu of ESRD drives profound gut dysbiosis. This leads to the overproduction of uremic toxins and compromises intestinal barrier integrity, facilitating the systemic translocation of these toxins and other pro-inflammatory bacterial products. These circulating factors subsequently promote cardiovascular pathology through the induction of systemic inflammation, oxidative stress, endothelial dysfunction, and direct cellular toxicity in vascular and myocardial tissues. Conclusion: Gut dysbiosis is significantly and consistently associated with a wide spectrum of adverse cardiovascular outcomes in patients with ESRD. These findings underscore the gut as a central organ in the pathophysiology of uremic cardiovascular disease and highlight the gut-kidney-heart axis as a crucial therapeutic target for mitigating the excessive cardiovascular risk in this vulnerable population.